The Correlation between Interleukin-6 and D-dimer in Severe and Critical COVID-19 Patients - Prihatni, Delita; Supriatin, Lastri; Suraya, Nida; Andriyoko, Basti (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Severe and critical COVID-19 patients are known to experience hyperinflammatory conditions and endothelial damage primarily characterized by increased levels of IL-6 and D-dimer. This group of patients is also considered at risk of experiencing hemostasis disorders including decreased platelet counts, prolonged PT and APTT, as well as increased fibrinogen. Therefore, this study aimed to determine the correlation between IL-6 and D-dimer in severe and critical COVID-19 patients. The relationship between IL-6 and other hemostasis parameters such as platelet count, PT, APTT, and fibrinogen were also analyzed. A descriptive-correlative observational design was used with a retrospective cross-sectional approach. The subjects were severe and critical COVID-19 patients at Hasan Sadikin Hospital, Bandung treated between January to December 2021 and met the inclusion and exclusion criteria. Secondary data were taken from medical records and the Laboratory Information System (LIS). Correlation analysis between IL-6 and D-dimer as well as hemostasis parameters was carried out using the Spearman test. The results showed that among the total 167 subjects, the median age was 60 years. The number of male subjects was 110 (65.86%), while the most common comorbidity was hypertension (45.51%). The analysis showed a very weak and insignificant correlation between IL-6 and platelets (r= -0.044; p=0.571), IL-6 and PT (r=0.115; p=0.137), IL-6 and APTT (r=0.109; p=0.159), as well as IL-6 and fibrinogen (r= -0.087; p=0.264). However, the correlation between IL-6 and D-dimer was significant (r= 0.199; p=0.010). Interleukin-6 did not correlate with hemostasis parameters but correlated with D-dimer. This means that IL-6 and D-dimer may provide information about the inflammatory response in COVID-19 patients and help monitor disease progression.